2014
DOI: 10.17843/rpmesp.2014.313.91
|View full text |Cite
|
Sign up to set email alerts
|

Comparación del hyper-CVAD con un régimen institucional en el tratamiento de la leucemia linfoblástica aguda del adulto en un hospital de México

Abstract: RESUMENCon el objetivo de evaluar la mortalidad y toxicidad del protocolo Hyper-CVAD utilizado como primera línea de tratamiento de la leucemia linfoblástica aguda se realizó un estudio de cohorte retrospectiva en pacientes de 40 años a menos durante marzo a septiembre de 2011 atendidos con el régimen Hyper-CVAD. La mortalidad y toxicidad se comparó con los resultados de los pacientes atendidos con el régimen institucional HGMLAL07 entre 2009 a 2012. Se incluyeron 18 pacientes, la mediana de edad fue de 26 año… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
3
1
1
Order By: Relevance
“…Another limitation of our study of a retrospective nature, is the scarce availability of certain immunophenotype markers such as aberrant myeloid markers; this precludes trustworthy correlation analyses between aberrant markers and the Philadelphia chromosome status, as well their inclusion in the survival analysis. ALL‐T cases were identified in 2.9%; which is less than previously reported by other authors in Mexico (5–10%) as well as in other countries (10–30%) . We do not have an explanation for this finding.…”
Section: Discussioncontrasting
confidence: 78%
See 3 more Smart Citations
“…Another limitation of our study of a retrospective nature, is the scarce availability of certain immunophenotype markers such as aberrant myeloid markers; this precludes trustworthy correlation analyses between aberrant markers and the Philadelphia chromosome status, as well their inclusion in the survival analysis. ALL‐T cases were identified in 2.9%; which is less than previously reported by other authors in Mexico (5–10%) as well as in other countries (10–30%) . We do not have an explanation for this finding.…”
Section: Discussioncontrasting
confidence: 78%
“…The most frequently used treatment protocol was hyper-CVAD, but the CR and relapse rates as well as the survival curves were inferior to those reported by developed societies [13][14][15][16] and this has been a constant feature in the country's publications [21,24]. Although we found that the AYA group had better CR rates (80.1%) in comparison with the adult and elderly adult group (65.6%), these rates are still low compared with the data reported by developed societies [13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sin embargo, en un estudio publicado en población colombiana, este esquema proporcionó resultados desalentadores con una sobrevida global mediana de menos de 11,3 meses, sobrevida libre de eventos de 7,34 meses y 61% de remisión completa (76). De igual manera, otros estudios latinoamericanos también informan una peor supervivencia al utilizar el mismo esquema quimioterapeútico (77,78), lo que evidencia que la respuesta a estos tratamientos se ve influenciada por múltiples factores, entre ellos el tipo de población.…”
Section: Inmunoterapia Celular Y Modulación De La Expresión De Cd20unclassified